Investigating the Impact of Some Inter-organizational Factors on Sustainability Reporting of the Pharmaceutical Companies Listed on the Tehran Stock Exchange - S. R. Masoumi; S. H. Salehnejad; A. Zabihi Zarinkalaei (حسابداری سلامت, 2018)
Introduction: Companies work as multidisciplinary institutions rather than fulfilling economic function exclusively. One of the challenging and notable issues is corporate sustainability reporting which reflects companies’ economic, social and environmental achievements. Method: This study is descriptive-correlational, a quantitative research based on the nature of the data and causal-ex post facto research in terms of time dimension. In order to measure the corporate sustainability reporting, the criteria of the Global Reporting Initiative and the indices specified in other studies were used. In this research, among inter-organizational factors affecting the sustainability reporting the profitability, sales growth, financial leverage, ownership distribution, and business complexity were selected and studied. The statistical population consists of the pharmaceutical companies listed on the Tehran Stock Exchange during the period of 2010-2016 and multivariate regression model has been administered to test the research hypotheses. Results: Profitability, ownership distribution, and business complexity have positive and significant impact on corporate sustainability reporting, but the sales growth and financial leverage do not impact corporate sustainability reporting significantly. Conclusion: According to the results of this research, as the company's profitability variable impacts on sustainability reporting more than other variables in pharmaceutical companies, it is suggested to investors and other users of financial reports to consider the influential factors presented in this study when they make decision on the extent of companies cooperation in activities related to the sustainability.